Is the estimated glomerular filtration rate formula useful for evaluating the renal function of Down syndrome?. Issue 8 (27th June 2021) - Nishino, Tomohiko; Endo, Shota; Miyano, Hiroki; Umeda, Chisato; Tomii, Yuji; Watanabe, Yoshitaka; Nakagawa, Mayu; Kakegawa, Daisuke; Fujinaga, Shuichiro
Abstract: Background: Children with Down syndrome (DS) have different growth rates compared with normal children. The present study examined the reliability of a general formula, Uemura's formula, utilized in normal Japanese children to estimate renal function (estimated glomerular filtration rate – eGFR) in children with DS. Methods: This study included 758 children aged 2–18 years with DS who visited our medical center. Patients with congenital heart disease, or congenital anomalies of the kidney or urinary tract detected via abdominal ultrasonography, chronic glomerulonephritis, and vesicoureteral reflux, etc., were excluded. Height and serum creatinine data gathered from 2421 examinations of 379 children with DS (224 boys and 155 girls) were used to evaluate Uemura's formula. Results: The mean eGFR was lower in children with DS than in children without DS. Stage II chronic kidney disease was indicated in 44.6% of examinations and stage III in 0.8%. The association of eGFR with age differed between sexes. Boys with DS showed a significant but weak negative correlation between eGFR and age ( r  = −0.273, P  < 0.001), whereas girls with DS showed a significant but very weak negative correlation ( r  = −0.111, P  < 0.001). Conclusions: A new eGFR formula that takes into account specific growth rates and puberty is needed for children with DS because general renal function evaluation formulas are inappropriate for these patients.